Stroke: prevalence and disability in Cotonou, Benin - Cossi, Marie-Joëlle; Gobron, Claire; Preux, Pierre-Marie; Niama, Didier; Chabriat, Hugues; Houinato, Dismand (My University, 2012)
BACKGROUND: Little is known about the burden of stroke in sub-Saharan Africa that may increase with the ongoing demographic and socioeconomic transition. This study aims to assess the prevalence of stroke, its related disability rate and consequences in the quality of daily life in an urban door- to-door survey in Cotonou, Benin. METHODS: A three-phase door-to-door study was performed in two districts of Cotonou with a broad range of socioeconomic income. A population of 15,155 individuals aged ≥15 years was evaluated. The first phase consisted in screening of stroke in the population using the modified WHO questionnaire, the second phase included the medical evaluation of all suspected cases, and in the third phase the diagnosis of stroke was confirmed by CT scan evaluation. RESULTS: Out of 15,155 subjects, 321 cases were identified as possible stroke cases. The diagnosis was confirmed in 70 cases. The crude prevalence of stroke was thus estimated to be 4.6/1,000 (8.7/1,000 and 7.7/1,000 adjusted to the WHO and SEGI World Population). The mean age of the patients at onset was 56 ± 13 years. Sixty percent of stroke survivors had a Rankin score ≥2, and CT scan was found abnormal in 90.0% of them. CONCLUSION: The stroke prevalence in urban areas of Cotonou is higher than that reported in other sub-Saharan countries, and the majority of stroke survivors present with good functional recovery and without severe disability in their everyday life.
Keywords: Stroke; prevalence; disability; Benin